1996
DOI: 10.1109/36.481897
|View full text |Cite
|
Sign up to set email alerts
|

A Markov random field model for classification of multisource satellite imagery

Abstract: Abstruct-A general model for multisource classification of remotely sensed data based on Markov Random Fields (MRF) is proposed. A specific model for fusion of optical images, synthetic aperture radar (SAR) images, and GIS (Geographic Information Systems) ground cover data is presented in detail and tested. The MRF model exploits spatial class dependencies (spatial context) between neighboring pixels in an image, and temporal class dependencies between different images of the same scene. By including the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
246
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(250 citation statements)
references
References 33 publications
0
246
0
4
Order By: Relevance
“…Several studies have shown that SAR data may provide information on structural features of the surface complementary to the spectral information in optical data, for instance [3,4,15,17,18]. It has thus been shown, that the discriminating power of SAR images is very much improved when they are used in combination with optical data.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies have shown that SAR data may provide information on structural features of the surface complementary to the spectral information in optical data, for instance [3,4,15,17,18]. It has thus been shown, that the discriminating power of SAR images is very much improved when they are used in combination with optical data.…”
Section: Introductionmentioning
confidence: 94%
“…They provide a flexible tool to include spatial context into image-analysis schemes in terms of minimization of suitable energy functions. While earlier algorithms for optimizing MRF energy, such as iterated conditional modes (ICM) and simulated annealing (Solberg, et al, 1996), (Tarabalka, et al, 2010b) were time consuming, more advanced methods, such as graph cuts ), (Li, et al, 2012) provided powerful alternatives from both theoretical and computational viewpoints, resulting in a growing use of the MRF-based segmentation techniques.…”
Section: Mrf-based Algorithmsmentioning
confidence: 99%
“…It iteratively considers every pixel , and assigns a (region or class) label to this pixel, which minimizes the local energy centered at . Solberg, et al (1996) applied the ICM optimization for multisource classification of optical, SAR and geographic information systems images. Farag, et al (2005) employed the ICM method for hyperspectral image classification.…”
Section: Simulated Annealing and Iterated Conditional Modesmentioning
confidence: 99%
“…Pixel-level fusion techniques can also be used to improve the efficiency of classification and detection algorithms. In general, pixel-level fusion methods can be classified into linear methods (Achalakul and Taylor 2001), nonlinear methods (Matsopoulos et al 1994, Matsopoulos and Marshall 1995, Mukhopadhyay and Chanda 2001, optimization techniques (Solberg et al 1996), neural networks (Zhang et al 2001, Shkvarko et al 2001) and image pyramids (Liu et al 2001).…”
Section: Introductionmentioning
confidence: 99%